(untitled) (Bangladesh Journal of Medical Biochemistry, 2024)
Recent studies have suggested a potential role of bilirubin as an antioxidant to protect diabetic patients from hyperglycemia-induced oxidative stress thereby preventing diabetic complications. Diabetic nephropathy is a serious microvascular complication which is determined by increased urinary albumin to creatinine ratio and reduced eGFR. The present work aimed to study the relation of the simple biochemical parameter of serum bilirubin level with the estimated glomerular filtration rate (eGFR) and spot urine albumin to creatinine ratio in diabetic patients with or without nephropathy. This cross sectional study was done in the department of Biochemistry and Molecular Biology, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) Academy from July 2017 to June 2018. We have taken 63 diabetic patients without nephropathy and 63 diabetic patients with nephropathy.Data about clinical and biochemical parameters (blood pressure, BMI, fasting serum glucose, estimated GFR, serum bilirubin and spot urine ACR etc.) were measured by appropriate methods. We used student’s t test and Pearson’s correlation coefficient to detect the relationship of serum bilirubin with other variables All statistical tests were considered at 5% level of significance. We found diabetic patients with nephropathy have significantly lower serum bilirubin (p<0.001) than diabetic patients without nephropathy (0.46±0.18 and 0.64± 0.21 mg/d respectively). Pearson’s correlation test showed that serum bilirubin positively correlated with eGFR (r=0.312, p=0.013) in diabetic patients with nephropathy. This study concluded that low serum bilirubin level is associated with eGFR in diabetic patients with nephropathy. Bangladesh J Med Biochem 2019; 12(2): 16-22